A note on decidability of reachability for conditional Petri nets - Țiplea, Ferucio Laurenţiu; Bădărău, Cristina (Acta Cybernetica, 2000)
The aim of this note is to prove that the reachability problem for Petri nets controlled by finite automata, in the sense of [5], is decidable.